THE EFFECT OF WOMEN'S AGE DURING PREGNANCY ON THE CASE OF HYPOSPADIAS IN CHILDREN - Nasution, Iqbal Pahlevi Adeputra; Lin, Chrysty (Indonesian Journal of Urology, 2023)
ABSTRACT Objective: The purpose of this study was to determine the effect of a woman’s age during pregnancy on the incidence of hypospadias in children. Material & Methods: This research is an analytic study with a case control design. The sampling technique is a non-probabilistic technique with consecutive sampling. This study was analyzed by univariate and bivariate. Results: From 62 samples, the number of hypospadias cases was 28 people (90.3%) with woman's age at pregnancy <35 years and 3 people (9.7%) with woman's age at pregnancy ≥ 35 years. While the number of controls was 29 people (93.5%) with woman's age at pregnancy <35 years and 2 people (6.5%) with woman's age at pregnancy ≥ 35 years. Conclusion: There is no significant relationship found in this research between a woman's age at pregnancy and the incidence of hypospadias in children. Keywords: Age, hypospadias, pregnancy.